Double Loop Problem Solving Learning Model on Statistical Material at MTS NU Nahdlatul Atfhal Kudus - Galih Kurniadi; Jayanti Putri Purwaningrum (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
At Mts NU Nahdlatul Atfhal Kudus, many students feel that statistical material is one of difficults subject. It looks at their statistical test results. This research aims to assess the implementation of double loop problemsolving learning model on statistical material at MTS NU Nahdlatul Atfhal Kudus in improving students’ mathematical problem solving abilities. The study was conducted in class VIII A (double loop problem solving learning model class) dan VIII B (expository learning class). The method that used in this research is quasi experimental research with nonequivalent control group design. The research instrument used is mathematical problem solving test. Data analysis used a N-gain normalized test to see an improvement in students' mathematical problem solving abilities in both research classes, descriptive statistic, normality test and parametric and non parametric test. The findings of this research is based on Mann-Whitney U, students 'mathematical problem solving abilities on statistical materials by applying double loop problem solving learning model are higher than the students' mathematical problem solving abilities that applied the expository learning.This shows that double loop problem solving learning model can improve students' mathematical problem solving abilities. Based on this results, it can be concluded that double loop problem solving learning model iseffective in statistical materialKeywords: double loop problem solving learning model, statistical material, mathematical problem solving abilities